Effectiveness Of Red Betel Leaf Ointment (Piper Crocatum, Ruiz & Pav) On Slash Wounds In White Mice - Yensuari Yensuari; Andriani Andriani (CV. Inara, 2024)
Normal wounds may heal on their own in some cases, but if there are obstructions in the way, the wound won't heal, making them more difficult to treat. The purpose of this study was to evaluate the phytochemical makeup of red betel plant leaves and the effectiveness of red betel extract in accelerating wound healing in white mice. 25 male white mice made up the animal population, which was divided into 5 groups, including 3 treatment groups. using red betel extract percentages of 15%, 30%, 45%, and 10%. a pair of control groups, one positive and the other negative. The control utilized a gel-based solution and 10% povidone iodine. The white mice's backs were cut into using a 1 cm2 incision. The data was gathered by observing the entire wound healing procedure from the inflammatory phase (redness, edema, and pus presence) through the proliferative phase. The current data were then assessed using a method called the Test of Homogeneity of Variances. The One Way Anova test is useful for determining whether or not there are meaningful changes in the data variance if the prerequisites for the parametric test are met. If the p value is less than or equal to 0.05, this test is significant. The LSD post hoc test also determines the most significant set of data. When testing the distribution, if abnormal data are discovered, another alternative method is using the Kruskal-Wallis test, which is followed by the Mann-Whitney test with a significant value of 0.05. Between the positive and negative control groups, redness (p=0.003), granulation tissue (p=0.038) on the third day, and wound area reduction (p=0.048) on the ninth day were all significantly different when red betel extract concentrations of 15%, 30%, and 45% were used. It may be concluded that giving white mice betel extract at a concentration of 46% accelerates the healing of wounds. According to phytochemical analysis, red betel extract contains alkaloids, flavonoids, saponins, and tannins, making it a potential natural antioxidant.